THE EFFECT OF THE COMPOSITION OF PALM SUCCUS BIOETHANOL AS A BLENDING AGENT IN PERTALITE (RON 90) FUEL ON THE PERFORMANCE OF A 4-STROKE GASOLINE ENGINE - Al Kautsar; Maulana Muhammad; Faisal Muhtadin; M Mahyuddin; L Lindawati (Politeknik Negeri Lhokseumawe, 2026)
The research titled “The Effect of Palm Sap Bioethanol Composition as an Additive in Pertalite RON 90 Fuel on the Performance of a 4-Stroke Gasoline Engine” was motivated by the increasing demand for energy and the high dependence on fossil fuels, which contribute to environmental pollution. Therefore, the utilization of renewable energy has become one of the solutions that can be developed, one of which is through the use of bioethanol derived from sugar palm sap as an alternative fuel. Sugar palm sap bioethanol has a sufficiently high alcohol content, making it a potential additive in gasoline to improve combustion quality. This study aims to analyze the effect of palm sap bioethanol blend compositions in Pertalite RON 90 fuel on the exhaust gas emission characteristics of a four-stroke gasoline engine. The research method employed was an experimental approach, involving RON (Research Octane Number) testing and exhaust gas emission testing on a gasoline engine using various fuel blend variations. The tests were conducted using a gas analyzer to measure exhaust emission parameters, including carbon monoxide (CO), hydrocarbons (HC), carbon dioxide (CO₂), oxygen (O₂), and the lambda value, which indicates the air-to-fuel ratio in the combustion process. The results of the study indicate that adding palm sap bioethanol to Pertalite fuel tends to reduce CO and HC emissions, suggesting more complete combustion within the combustion chamber. Additionally, the increase in CO₂ and O₂ levels indicates improved oxidation during combustion as the percentage of bioethanol in the fuel mixture increases. The lambda values obtained are within a range close to stoichiometric conditions, indicating a better balance of the air-to-fuel ratio during the combustion process. Based on these research results, it can be concluded that sugar palm sap bioethanol has the potential to be used as a more environmentally friendly fuel additive in gasoline engines without requiring significant engine modifications. Keywords: palm sap bioethanol, Pertalite RON 90, exhaust emissions, gasoline engines, alternative fuels.